Evaluation and Examination of a Possible Shoe-polish Trace in a Hold-up Case - Line Gueissaz; Tacha Hicks; Cyril Muehlethaler; Geneviève Massonnet (Wolters Kluwer Medknow Publications, 2016)
In this article, we show how the Bayesian framework can be applied to a hold-up case involving a possible shoe-polish trace according to one of the parties. This article highlights the importance of interpreting data from the beginning of the examination through the preassessment steps. Once a set of alternative propositions in agreement with the information provided by the parties is chosen, one can establish what is needed in the case. Here, limited data were available to assign factors such as transfer and rarity of the traces. Consequently, we showed how specific case-tailored experiments provide meaningful data for evaluation. In this case, the police had observed a trace on the jacket of a person who reported to have been pushed with the offender's gun during the hold-up attempt. When the jacket was submitted to our laboratory, the exact nature of the trace was unknown. Particles from this trace were collected and analyzed by stereomicroscopy, microscopy, and infrared spectroscopy. The obtained results supported that this trace was waxy material. The literature dealing with the analysis of waxy materials generally uses solvent extraction-based methods. Here, as our analytical sequence allowed a good discrimination of different waxy products of known origin, we considered that this methodology was adequate. Moreover, it did not involve any extraction step that could lead to undesired compounds from the substrate (e.g., dyes and additives). This article therefore suggests an alternative analytical sequence for the analysis of such material in casework.